Astonishing diversity revealed: an annotated and illustrated inventory of Nudipleura (Gastropoda: Heterobranchia) from Mozambique - Tibiriçá, Yara; Pola, Marta; Cervera, Juan Lucas (Zootaxa, 2017)
This paper provides the first comprehensive annotated and illustrated inventory of Nudipleura from Mozambique. A total of 267 species are recorded, including 61 putative new species, documented over a period of seven years from several localities along the coast. At least 20 species need further investigation through molecular and taxomic analysis. Of the 186 confirmed described species, 118 are new records for the Mozambican fauna. Sampling was carried in tidal reefs and depths up to 60m on the subtropical and tropical coast of Mozambique. The most representative families were Chromodorididae (69 species), Discodorididae (30 species), Facelinidae (23 species) and Phyllididae (16 species). Nevertheless, a vast area of Mozambique remains unexplored, thus it is likely that the species documented here represent only a fraction of the true Nudipleura diversity of the country.